Establishing the content validity of PROMIS Pediatric pain interference, fatigue, sleep disturbance, and sleep-related impairment measures in children with chronic kidney disease and Crohn's disease - Christopher B. Forrest; Kathryn D. Forrest; Jennifer L. Clegg; Anna de la Motte; Sandra Amaral; Andrew B. Grossman; Susan L. Furth (SpringerOpen, 2020)
Abstract Background PROMIS Pediatric patient-reported outcome measures were developed with children from the general population, and their content validity has not been established in children with chronic disease. This study was done to evaluate the content validity of the PROMIS Pediatric Pain Interference and Fatigue measures in children 8-17 years-old with Crohn's disease and the PROMIS Pediatric Fatigue, Sleep Disturbance, and Sleep-related Impairment measures for children 8-17 years-old with chronic kidney disease. Methods We conducted semi-structured interviews with individuals affected by Crohn's disease and chronic kidney disease. The interviews were done to elicit children's lived experiences of the PROMIS outcomes of interest. We used deductive content analysis to contrast the participants' reports of their symptoms and impacts on daily life with existing conceptual frameworks for the PROMIS measures, each of which was developed with input from children in the general population. Results On average, we elicited an average of 7 pain interference and 7 fatigue concepts from Crohn's disease participants (n = 37), while chronic kidney disease participants (n = 26) provided 9 concepts for fatigue, 4 for sleep disturbance, and 7 for sleep-related impairment. Concept saturation was achieved after 16-19 interviews across the four PROMIS measures. Children with these two chronic health conditions reported the same breadth and types of lived experiences as children from the development samples drawn from the general population. Conclusion The study supports the content validity of several PROMIS Pediatric measures for children with Crohn's disease and chronic kidney disease. These findings provide evidence that PROMIS Pediatric measures, developed as universally relevant patient-reported outcomes, may be more broadly applicable to children with chronic disease.